2014
DOI: 10.1097/ss.0000000000000056
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Solute Dispersion Coefficients in Porous Media at Low Pore Water Velocities

Abstract: The relationship between solute dispersion coefficient (D mech ) and pore water velocity during chloride transport in porous media with different particle characteristics at low pore water velocities (u < 1 cm min −1 ), relevant for ground water flow conditions, was investigated. Data for 29 porous media with very different particle shapes (ranging from almost spherical to very angular) and particle sizes (0.088-12 mm) at different velocities (340 breakthrough curves) were used in the analyses. The analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…These figures confirm the trends observed in Tables 3 and 4. The results of this work reveal a linear relationship between the dispersion coefficient and fluid velocity as shown in Equations ( 1) and (2), inconsistent with the previous findings of the nonlinear relationship [35][36][37][38]. The cause of this difference can be attributed to the grain shape and fluid velocity.…”
Section: Equations Of Dispersion Coefficient In Corescontrasting
confidence: 99%
See 2 more Smart Citations
“…These figures confirm the trends observed in Tables 3 and 4. The results of this work reveal a linear relationship between the dispersion coefficient and fluid velocity as shown in Equations ( 1) and (2), inconsistent with the previous findings of the nonlinear relationship [35][36][37][38]. The cause of this difference can be attributed to the grain shape and fluid velocity.…”
Section: Equations Of Dispersion Coefficient In Corescontrasting
confidence: 99%
“…The longitudinal dispersion coefficient D L does not vary linearly with water velocity Pugliese and Poulsen [36] Measuring the dispersion coefficient in a series of porous media with different grain sizes and shapes…”
Section: Research Methods Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the dispersion coefficient continued to decline when the density difference of the displaced fluid increased or the viscosity ratio decreased. Pugliese and Poulsen 33 used a series of particles with different shapes and sizes as porous media to conduct experimental research on fluid dispersion. The results show that the closer the porous media particles are to the sphere, the more obvious the linear relationship between the dispersion coefficient and water flow velocity is.…”
Section: Introductionmentioning
confidence: 99%